Antiinflammatory and antioxidant effects of Jungia rugosa Less (matico de puna) leaves' flavonoids in rats - Enciso, Edwin (2011)
Objectives: To determine anti-inflammatory and antioxidant activities of Jungia rugosa Less leaves flavones’ fraction. Design: Experimental. Setting: Faculties of Medicine and Pharmacy and Biochemistry, National University of San Marcos, Lima, Peru. Biological material: Flavones fraction extracted from Jungia rugosa Less leaves and rats. Interventions: Jungia rugosa Less leaves collected in Condorcunca’s hill at 3 500 m.a.s.l., Quinua district, Ayacucho department. The anti-inflammatory activity was assessed in vivo in carrageenan-induced paw edema model and 1, 6 interleukins serum levels and C reactive protein (CRP) were measured in blood; granuloma was induced according to Sedwicks and studied by histopathology. The antioxidant effect was investigated in vitro by 1,1- diphenyl-2-picrylhydrazyl (DPPH) radical neutralization. Main outcome measures: Anti-inflammatory and antioxidant effects. Results: Inflammation reduced in 43,8% and 1,6 interleukins and CRP levels decreased respectively 80%, 90% and 78% compared to control, in dose-dependent effect (p<0,05), with 97,7% DPPH radicals inhibition. Conclusions: Flavones fraction extracted from Jungia rugosa Less leaves is anti-inflammatory and antioxidant.